Revisiting Three Decades Of Educational Research In Iran: A Bibliometric Analysis - Rouhollah Khodabandelou; Nader Aleebrahim; Azadeh Amoozegar; Golnar Mehran (Comparative Education Society of Iran ( CESIR), 2019)
Educational research is one of the fundamental infrastructure factors that improve sustainable development of a country. The aim of this mixed method study was to explore research trends by employing scintiometric approach in order to visualize and structure Iranian educational research litrature. Based on the bibliometric technique, all 3,812 existing documents from 2000 to 2018 are investigated. Additionally, we employ bibliometric analyses on a sample of 100 most cited papers to identify articles of higher quality or impact. Major trends in Iranian educational research literature which have been investigated including variations across publication years, identifying active research areas, and the most prolific authors. The results of the thematic analysis showed that educational psychology in the schools, technology based research in higher education, improvement in language learning and micro view to teaching and learning are valuable Iranian educational research themes. Implications for research institutions, education policy makers, and educational researchers are discussed